Energy Access, Efficiency, and Poverty : How Many Households Are Energy Poor in Bangladesh? - Barnes, Douglas F.; Khandker, Shahidur R.; Samad, Hussain A. (2012)
Access to energy, especially modern sources, is a key to any development initiative. Based on cross-section data from a 2004 survey of some 2,300 households in rural Bangladesh, this paper studies the welfare impacts of household energy use, including that of modern energy, and estimates the household minimum energy requirement that could be used as a basis for an energy poverty line. The paper finds that although the use of both traditional (biomass energy burned in conventional stoves) and modern (electricity and kerosene) sources improves household consumption and income, the return on modern sources is 20 to 25 times higher than that on traditional sources. In addition, after comparing alternate measures of the energy poverty line, the paper finds that some 58 percent of rural households in Bangladesh are energy poor, compared with 45 percent that are income poor. The findings suggest that growth in electrification and adoption of efficient cooking stoves for biomass use can lower energy poverty in a climate-friendly way by reducing carbon dioxide emissions. Reducing energy poverty helps reduce income poverty as well.